1998
DOI: 10.1080/10691898.1998.11910604
|View full text |Cite
|
Sign up to set email alerts
|

Training Doctoral Students in Educational Statistics in the United States: A National Survey

Abstract: Although numerous research studies have focused on issues related to the teaching of statistics, few studies have focused on the training of people who may become statistics teachers. The purpose of this study was to examine doctoral students' preparation in statistics in the field of education. A national survey was conducted of twenty-seven quantitative methods (QM) programs. One QM professor from each program was identified and asked to describe and evaluate the training of QM and non-QM doctoral students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Studies have found a range of requirements. Curtis and Harwell () examined the quantitative methods requirements of 21 doctoral programs in the United States for both students who specialized in quantitative methods and those who did not. They found that 43% of institutions did not require students to take statistics courses if they were not specializing in quantitative research.…”
Section: Reviews Of Statistical Literacy In Related Fieldsmentioning
confidence: 99%
“…Studies have found a range of requirements. Curtis and Harwell () examined the quantitative methods requirements of 21 doctoral programs in the United States for both students who specialized in quantitative methods and those who did not. They found that 43% of institutions did not require students to take statistics courses if they were not specializing in quantitative research.…”
Section: Reviews Of Statistical Literacy In Related Fieldsmentioning
confidence: 99%
“…Curtis and Harwell (1998) conducted a similar study, reviewing the statistics training sequences of 27 quantitative methods doctoral programs. Professors generally reported that doctoral students in education received training in traditional methods such as multiple regression and analysis of variance but generally did not receive training in more recent methods such as multilevel modeling.…”
Section: Quantitative Training Curriculummentioning
confidence: 99%
“…conduct high-quality educational research. The methodology requirements in doctoral programs can be informed by reviews such as the present report (see Curtis & Harwell, 1998;Guo & Nitko, 1996).…”
Section: Education and Psychology As A Wholementioning
confidence: 99%